2020
DOI: 10.3389/fpls.2020.577475
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rf9, a Gene Contributing to the Genetic Complexity of Fertility Restoration in Hybrid Wheat

Abstract: Wheat (Triticum aestivum L.) is a self-pollinating crop whose hybrids offer the potential to provide a major boost in yield. Male sterility induced by the cytoplasm of Triticum timopheevii is a powerful method for hybrid seed production. Hybrids produced by this method are often partially sterile, and full fertility restoration is crucial for wheat production using hybrid cultivars. To identify the genetic loci controlling fertility restoration in wheat, we produced two cytoplasmic male-sterile (CMS) backcross… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…The dominance of Rf8 localized on chromosome 2DS was verified by Sinha et al [36]. Another major dominant restorer gene, Rf9, was detected in the subtelomeric region of chromosome 6AS [39]. Melonek et al [47] recently identified Rf1 and Rf3 via genetic mapping, comparative sequence analyses, and functional studies.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The dominance of Rf8 localized on chromosome 2DS was verified by Sinha et al [36]. Another major dominant restorer gene, Rf9, was detected in the subtelomeric region of chromosome 6AS [39]. Melonek et al [47] recently identified Rf1 and Rf3 via genetic mapping, comparative sequence analyses, and functional studies.…”
Section: Introductionmentioning
confidence: 95%
“…To date, eight fertility restorer genes (Rf1-Rf6 and Rf8-Rf9) that restore the production of normal pollen in wheat with the T. timopheevii sterilizing cytoplasm have been identified and mapped on the following seven wheat chromosomes: 1A (Rf1), 1BS (Rf3), 2DS (Rf8), 6A (Rf6), 6AS (Rf9), 6B (Rf6 and Rf4), 6D (Rf5), 7B (Rf7), and 7D (Rf2) [29][30][31][32][33][34][35][36][37][38][39]. There is some uncertainty regarding the nomenclature of Rf2, Rf3, Rf4, and Rf6 [40].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are certain aspects of CMS systems, including timopheevii CMS, that render these systems more complex for hybrid seed production in wheat. First, various studies have revealed that combinations of two or three and perhaps more Rf genes are needed for complete fertility restoration of CMS in wheat [ 75 , 76 , 77 ]. To add to that complexity, epistatic interactions among Rfs and between Rfs and modifier loci have also been highlighted by several studies [ 78 ].…”
Section: Hybridization Systems For Hybrid Seed Production In Wheatmentioning
confidence: 99%